2009
DOI: 10.1177/153303460900800510
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiosurgery for Pelvic Relapse of Gynecologic Malignancies

Abstract: Clinical management of pelvic relapses from gynecologic malignancies remains challenging. Bulky pelvic relapses often lead to symptomatic cancer-related complications and poor clinical outcomes. Options may be limited by prior surgical, chemotherapeutic, and radiation treatment. Stereotactic body radiosurgery is a novel treatment modality which allows high radiation dose delivery in a non-coplanar fashion with sub-millimeter precision utilizing a linear accelerator mounted on a robotic arm. This study details … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 34 publications
2
50
0
Order By: Relevance
“…7,8,15 Data question radiobiological effects and mode of cell death resulting from SBRT. Small clinical studies have shown that ablative radiation doses provided by SBRT produce targeted disease control rates exceeding 90%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8,15 Data question radiobiological effects and mode of cell death resulting from SBRT. Small clinical studies have shown that ablative radiation doses provided by SBRT produce targeted disease control rates exceeding 90%.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical target volume (CTV) expansion by 0.5 cm, resulting in a larger planning target volume (PTV), is associated with increased target control without undue normal tissue injury. 7,8 Further reduction in the probability of geographic miss may be achieved by incorporation of 2- …”
Section: -13mentioning
confidence: 99%
See 1 more Smart Citation
“…Innovative technology effectively pairing clinical radiation accelerators to helical scanners (Tomotherapy [25,26]) or to robotic arm mounts (Cyberknife®, [27][28][29][30]) with respiratory gating [31,32] has been a market force for recently-realized radiotherapeutic gains in gynecologic radiation oncology [33]. For purposes of discussion here, the subclass of stereotactic radiosurgery dealing with robotics [Cyberknife®, Accuray (Sunnyvale, CA, USA)] will be the focus given the preponderance of clinical data accumulated worldwide [27][28][29][30]. Robotic cyberknife stereotactic body radiosurgery for gynecologic cancers most commonly involves ablative dose (>8 Gy) delivery [34,35], over a 30-60-min irradiation time span, with sub-millimeter precision [36,37] and with motion tracking [38] all in an effort to avoid injury to normal abdominopelvic tissues.…”
Section: Rationale For Use In Gynecologic Malignanciesmentioning
confidence: 99%
“…For purposes of discussion here, the subclass of stereotactic radiosurgery dealing with robotics [Cyberknife®, Accuray (Sunnyvale, CA, USA)] will be the focus given the preponderance of clinical data accumulated worldwide [27][28][29][30]. Robotic cyberknife stereotactic body radiosurgery for gynecologic cancers most commonly involves ablative dose (>8 Gy) delivery [34,35], over a 30-60-min irradiation time span, with sub-millimeter precision [36,37] and with motion tracking [38] all in an effort to avoid injury to normal abdominopelvic tissues. Paramount to the integration of robotic stereotactic body radiosurgery in clinical radiation oncology practice is better understanding of natural systems of DNA damage repair.…”
Section: Rationale For Use In Gynecologic Malignanciesmentioning
confidence: 99%